Enantioselective Access to Bicyclo[4.2.0]octanes by a Sequence of [2+2] Photocycloaddition/Reduction/Fragmentation. Issue 38 (23rd August 2013) - Yin, Guoyin; Herdtweck, Eberhardt; Bach, Thorsten
<x xml:space="preserve">Abstract</x> Tricks of the trade: Because intramolecular Cu‐catalyzed access to bicyclo[4.2.0]octanes is not feasible, an oxygen bridge was introduced to facilitate the [2+2] photocycloaddition. Starting from compounds similar to 1, products such as 2 could be obtained enantioselectiviely in three steps after ring‐opening metathesis (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>